From Interseismic Deformation With Near-Repeating Earthquakes to Co-Seismic Rupture: A Unified View of the 2020 Mw6.8 Sivrice (Elazig) Eastern Turkey Earthquake - Konca, A. Ozgun; Karabulut, Hayrullah; Guvercin, Sezim Ezgi; Eskikoy, Figen; Ozarpac, Seda; Ozdemir, Alpay; Floyd, Michael; Ergintav, Semih; Dogan, Ugur (AMER GEOPHYSICAL UNION, 2021)
The East Anatolian Fault (EAF) is a left-lateral transform fault accommodating the relative motion between the Anatolian and Arabian plates. On January 24, 2020, M(w)6.8 Sivrice (Elazig) earthquake is the largest event that occurred along the EAF since the nineteenth century. The earthquake provides a unique opportunity to capture a critical stage of the seismic cycle from the interseismic deformation to co-seismic rupture. In this study, we examine the relationship between the interseismic fault activity and co-seismic behavior of the earthquake. A kinematic model of the earthquake obtained from strong-motion, GNSS and teleseismic waveforms along with static displacements from GNSS and InSAR data shows that the mainshock ruptured only 45 km of the 95 km long Sivrice-Puturge segment. Rupture initiated adjacent to the interseismically weakly coupled northeastern section and propagated unilaterally toward southwest with a rupture velocity of similar to 2.5 km/s, stopping similar to 30 km before the southwestern segment boundary. The earthquake did not generate any surface offsets. We identified 4 long-term near-repeating earthquake clusters beneath the highest co-seismic slip zone adjacent to the northeastern creeping section. The mainshock was dynamically triggered by a M similar to 5.4 foreshock located within the zone of near-repeating earthquakes. We suggest that creep along the weakly coupled section of the fault loaded the neighboring locked section leading to the repeating earthquakes below the locked zone. The earthquake partially ruptured a fault segment characterized by high rate of diffuse seismicity, structural complexities and heterogeneous coupling, leading to a source characterized by a complex source time function with relatively slow rupture velocity.
Keywords: 2020 Sivrice (Elazig) earthquake; earthquake source; seismicity; SAN-ANDREAS FAULT; HECTOR MINE; SLIP; SEGMENTATION; CALIFORNIA; DEPTH; GPS; ACCUMULATION; RECURRENCE; GEOMETRY; Geochemistry & Geophysics